2012
DOI: 10.3160/0038-3872-111.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon Storage in Restored Salt Marshes in Huntington Beach, California

Abstract: There is a growing interest in managing wetland restoration and conservation projects to maximize carbon sequestration. We measured soil organic carbon storage and methane flux from two southern California salt marshes which had been restored for 2 and 22 years. We hypothesized that organic carbon would accumulate following restoration and that methane flux would be negligible in both sites. While methane flux was minimal, soil organic carbon content was generally higher in the more recently restored site. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
0
15
1
Order By: Relevance
“…Two head escape samples were collected in 15 -30 min interval for each chamber from six locations. Samples were transported on the same day of collected gas samples to the School of Earth and Environmental Sciences Lab, Chapman University, Orange, CA for CO 2 and CH 4 analysis using gas chromatograph equipped with a flame ionization detector (SRI Instrument/1-mL sample loop, 100˚C column temperature/using GHG Standard = 1 ppm CH 4 ; 351 ppm CO 2 ). Laboratory blank was analyzed at the end of field gas sampling day along with five laboratory duplicates on June 13th, 2013.…”
Section: Analysis and Samplingmentioning
confidence: 99%
See 3 more Smart Citations
“…Two head escape samples were collected in 15 -30 min interval for each chamber from six locations. Samples were transported on the same day of collected gas samples to the School of Earth and Environmental Sciences Lab, Chapman University, Orange, CA for CO 2 and CH 4 analysis using gas chromatograph equipped with a flame ionization detector (SRI Instrument/1-mL sample loop, 100˚C column temperature/using GHG Standard = 1 ppm CH 4 ; 351 ppm CO 2 ). Laboratory blank was analyzed at the end of field gas sampling day along with five laboratory duplicates on June 13th, 2013.…”
Section: Analysis and Samplingmentioning
confidence: 99%
“…Therefore, wetland and salt marsh ecosystems have triggered interest due to the fact that they are a source for methane (CH 4 ) and nitrous oxide (NO 2 ) production carrying on a biologically active surface, and operating as greenhouse gas sink through photosynthetic absorbing and incorporating of CO 2 and consequently storage in long-lasting biomass. The salt marsh biota trap sediment (mostly clay and silt) fine particles, organic material, and trace metals, allowing large amount of plant growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously measured soil organic carbon storage in two restored salt marshes in Huntington Beach, California (Keller et al 2012). This work showed that soil organic carbon was generally higher in a marsh that had been restored for two years than in an adjacent marsh that had been restored for 22 years.…”
mentioning
confidence: 97%